Frequency and predictors of the lupus low disease activity state in a multi-national and multi-ethnic cohort. Issue 1 (December 2016) - Golder, Vera; Kandane-Rathnayake, Rangi; Hoi, Alberta; Huq, Molla; Louthrenoo, Worawit; An, Yuan; Li, Zhan; Luo, Shue; Sockalingam, Sargunan; Lau, Chak; Lee, Alfred; Mok, Mo; et al.
Abstract Background Systemic lupus erythematosus (SLE) is a chronic heterogeneous disease with considerable burden from disease activity and damage. A novel clinical treatment target in the form of the lupus low disease activity state (LLDAS) has been recently reported, with retrospective validation showing that time spent in LLDAS translates to reduced damage accrual. The objectives of this study were to describe the frequency and identify the predictors of attaining LLDAS in a large multinational cohort of patients with SLE. Methods Data were collected at the recruitment visit in patients with SLE enrolled in a longitudinal study in nine countries. Data were analysed cross-sectionally against the recently published definition of LLDAS, and the frequency and characteristics associated with presence of LLDAS were determined. Stepwise multivariable logistic regression was used to determine predictors of LLDAS. Results Of the 1846 patients assessed, criteria for LLDAS were met by 44 %. Patients with shorter disease duration were less likely to be in LLDAS (OR 0.31, 95 % CI 0.19–0.49, p  < 0.001). Likewise, patients with a history of discoid rash (OR 0.66, 95 % CI 0.49–0.89, p  = 0.006), renal disease (OR 0.60, 95 % CI 0.48–0.75, p  < 0.001), elevated double stranded DNA (OR 0.65, 95 % CI 0.53–0.81, p  < 0.001) or hypocomplementaemia (OR 0.52, 95 % CI 0.40–0.67, p  < 0.001) were less likely to be in LLDAS. When countries were compared, higher national social wealth (OR 1.57, 95 % CI 1.25–1.98, p  < 0.001) as measured by the gross domestic product per capita was positively associated with LLDAS, but ethnicity was not. Conclusion The lupus low disease activity state is observed in less than half of patients with SLE at a single point in time. Disease duration and phenotype, and national social wealth, are predictive of LLDAS.